Learning to Be a Father: How Do We Do It? Isn't there a Manual Somewhere? - Garett D. Evans; Kate Fogarty (EDIS)
Learning to be a good father is not for wimps. It takes time, energy, interest, and responsibility. Most of all, it takes you loving your child. When raising a child, no two days are the same, each day brings new questions and new challenges. It often leaves us asking ourselves: "Where and how do we learn to become a good father?" This document is FCS2138, one of a series of the Family, Youth, and Community Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication: December 1999. Revised: July 2005.